Changing language mindsets about modern languages: a school intervention. Issue 5 (2nd September 2020) - Lanvers, Ursula
ABSTRACT: In the context of the UK language learning crisis, several studies have aimed to influence student attitude towards languages via school interventions, with mixed results. A six-session tacking diverse metalinguistic issues (e.g. cognitive benefits of language learning, world languages) was carried out in three secondary schools in England, using both whole-class and small-group teaching. The study included a hitherto unmet aim, that of changing mindsets in mixed-ability settings, including students with the most negative language mindsets. Pre-post differences reveal that beliefs about language learning improved more than self-efficacy. Inclination to continue modern foreign language (MFL) study improved more in those students initially most disinclined to continue. Given the well-known gender divide in MFL uptake, it was pleasing to note that the intervention showed greater effect on boys than girls. Qualitative and quantitative data suggest that the intervention might have had a small 'equalising' effect in gender differences, in that boys' self-efficacy improved more than girls'. The study concludes that the dual delivery (whole-class teaching and in-school mentoring, delivered by older students in the same school) offers a promising format, but that, in order to achieve greater effects, more contact time and more mentor preparation are needed.